2023
DOI: 10.1002/jnr.25195
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sensorimotor cortex oscillatory activity by orexin‐A in the ventrolateral preoptic area of the hypothalamus reflect increased muscle tone

Abstract: Orexin-A (OXA) is a hypothalamic neuropeptide implicated in the regulation of wakefulness, appetite, reward processing, muscle tone, motor activity, and other physiological processes. The broad range of systems affected stems from the widespread projections of orexin neurons toward multiple brain regions regulating numerous physiological processes. Orexin neurons integrate nutritional, energetic, and behavioral cues and modulate the functions of target structures. Orexin promotes spontaneous physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 180 publications
0
1
0
Order By: Relevance
“…However, in the current study, orexin DRN enhanced SPA only during the first hour post injection, ruling out any effect of central fatigue in our study. In addition, we have recently demonstrated that the central injection of orexin enhances the excitability of the motor system in the brain [116], suggesting that DRN orexin-induced enhancement SPA may result from heightened brain motor preparedness. Overall, 5HT signaling has a complex role in the modulation of motor behavior and the current data suggest that the orexin-DRN pathway positively modulates SPA.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, orexin DRN enhanced SPA only during the first hour post injection, ruling out any effect of central fatigue in our study. In addition, we have recently demonstrated that the central injection of orexin enhances the excitability of the motor system in the brain [116], suggesting that DRN orexin-induced enhancement SPA may result from heightened brain motor preparedness. Overall, 5HT signaling has a complex role in the modulation of motor behavior and the current data suggest that the orexin-DRN pathway positively modulates SPA.…”
Section: Discussionmentioning
confidence: 99%